The Impact of Career Plateau and Organizational Support on Work Performance Through Organizational Justice and Employee Satisfaction At the Samsat Offices of Pidie and Pidie Jaya Regency - Herlina; Adam, Muhammad; Mukhlis, (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to examine the impact of career plateau and organizational support on work performance, with organizational justice and employee satisfaction serving as mediating variables, at the SAMSAT offices in the Pidie and Pidie Jaya districts. The research was conducted at the One-Stop Integrated Administration System (SAMSAT) offices in Pidie and Pidie Jaya. The population for this study consisted of all SAMSAT employees from both districts, totaling 113 individuals. The sampling technique employed was Total Sampling, where every member of the population had an equal chance of being selected as a sample. Data were collected using a Likert scale and analyzed using Partial Least Squares (PLS). Descriptive analysis revealed that career plateau, organizational support, organizational justice, employee satisfaction, and work performance at the SAMSAT offices in Pidie and Pidie Jaya were not functioning optimally. The results of direct testing showed that job satisfaction had a significant effect on work performance, while career plateau and organizational support did not directly influence work performance. Organizational justice was found to significantly affect job satisfaction, and organizational support contributed to enhancing perceptions of organizational justice. However, no direct effects of career plateau and organizational support on work performance were identified through the mediating pathways of organizational justice and job satisfaction. The practical implication of these findings is that organizations should prioritize improving employee job satisfaction through career development, enhanced compensation, and strengthening organizational support. Additionally, it is crucial to ensure clear career paths and development opportunities to mitigate feelings of stagnation (career plateau) among employees. By addressing these factors, organizations can enhance employee satisfaction and overall performance.